Scaling range sizes to threats for robust predictions of risks to biodiversity - Keith, David A.; Akçakaya, H. Resit; Murray, Nicholas J. (Conservation biology, 2018)
Assessments of risk to biodiversity often rely on spatial distributions of species and ecosystems. Range-size metrics used extensively in these assessments, such as area of occupancy (AOO), are sensitive to measurement scale, prompting proposals to measure them at finer scales or at different scales based on the shape of the distribution or ecological characteristics of the biota. Despite its dominant role in redlist assessments for decades, appropriate spatial scales of AOO for predicting risks of species' extinction or ecosystem collapse remain untested and contentious. There are no quantitative evaluations of the scalesensitivity of AOO as a predictor of risks, the relationship between optimal AOO scale and threat scale, or the effect of grid uncertainty. We used stochastic simulation models to explore risks to ecosystems and species with clustered, dispersed, and linear distribution patterns subject to regimes of threat events with different frequency and spatial extent. Area of occupancy was an accurate predictor of risk (0.81<|r|<0.98) and performed optimally when measured with grid cells 0.1-1.0 times the largest plausible area threatened by an event. Contrary to previous assertions, estimates of AOO at these relatively coarse scales were better predictors of risk than finer-scale estimates of AOO (e.g., when measurement cells are <1% of the area of the largest threat). The optimal scale depended on the spatial scales of threats more than the shape or size of biotic distributions. Although we found appreciable potential for grid-measurement errors, current IUCN guidelines for estimating AOO neutralize geometric uncertainty and incorporate effective scalingprocedures for assessing risks posed by landscape-scale threats to species and ecosystems. La evaluación de los riesgos para la biodiversidad generalmente depende de la distribución espacial de las especies y los ecosistemas. Las medidas del rango de extensión, como el área de ocupación (ADO), que se utilizan ampliamente en estas valoraciones son sensibles a la escala de medición, lo que genera propuestas para medirlas a escalas más finas o a diferentes escalas con base en la forma de distribución o en las características ecológicas de la biota. A pesar de su papel dominante en las valoraciones de listas rojas durante décadas, las escalas espaciales apropiadas del ADO para predecir el riesgo de extinción de las especies o el colapso de un ecosistema sigue siendo polémico y sin ser probado. No hay evaluaciones cuantitativas de la sensibilidad de escala del ADO como pronóstico de los riesgos, la relación entre la escala óptima del ADO y la escala de la amenaza, o el efecto de incertidumbre de cuadrícula. Utilizamos modelos de simulación estocástica para explorar los riesgos para los ecosistemas y las especies con patrones de distribución agrupada, dispersa y linear sujetos a regímenes de eventos amenazantes con frecuencias y extensiones espaciales diferentes. El área de ocupación fue un pronosticador preciso del riesgo (0.81<|r|<0.98) y actuó óptimamente cuando se midió con celdas de cuadrícula de 0.1 -1.0 veces la mayor área plausible amenazada por un evento. Contrario a aseveraciones previas, los estimados del ADO a estas escalas relativamente burdasfueron mejore pronosticadores del riesgo que los estimados del ADO a escalas más finas (p. ej. cuando las celdas de medición son <1% del área de la mayor amenaza). La escala óptima dependió de las escalas espaciales de las amenazas más que de la forma o el tamaño de las distribuciones bióticas. Aunque encontramos un potencial apreciable para los errores de medida de celda, las pautas actuales de la UICNpara la estimación del ADO neutralizan la incertidumbre geométrica e incorporan procedimientos efectivos de modificación de escala para la valoración de los riesgos presentados por las amenazas a escala de paisaje para las especies y los ecosistemas. 对生物多祥性面临风险的评估通常依赖于物种和生态系统的空间分布。在这类评估中广泛使用的分布范围大 小的度量，例如占有面积 (AOO), 对测量尺度很敏感，这提示我们应基于分布区形状或生物区生态特性在更精细 的尺度或不同尺度上进行测量。尽管几十年来 AOO 在红色名录评估中占有关键地位，然而用于预测物种灭绝 风险或生态系统崩溃的AOO合适的空间尺度还未得到检验且尚存在争议。AOO 作为风险预测指标的尺度敏 感性、最适 AOO 尺度和胁迫尺度的关系，以及网格不确定性的影响，目前都没有进行定量评估。我们用随机模 拟模型来探究生态系统和聚群分布、分散分布和线性分布的物种面临的风险，同时考虑它们受到的不同频率和 空间尺度的胁迫事件。占有面积是准确的风险预测指标（0.81<|r|<0.98)，当在测量的网格单元大小为受胁迫 影响的最大可能面积的 0.1-1.0 倍时，预测效果最好。与之前的认识相反，AOO 估计值在相对粗糙的尺度上比在 精细尺度上(如测量单元大小<1%最大胁迫面积时) 可以更好地预测风险。最优尺度更多地依赖于胁迫的空间尺 度，而不是生物分布区的形状或大小。尽管我们发现网格测量有很大潜在的误差，但当前 IUCN 估计 AOO 的指 导原则抵消了几何不确定性，且整合了确定尺度的有效程序，来评估景观尺度的胁迫对物种和生态系统产生的风 险